Pengaruh Motivasi Terhadap Kinerja Karyawan UKM Keripik Cinta Mas Hendro - Rani Febriyanni; Hade Chandra Batubara; Muslim Marpaung (Jurnal EMT KITA, 2023)
One of the activities of UKM in the trade sector in Langkat Regency, Air Hitam Village, Gebang Sub-district is the snack food industry named Kripik Cinta Mas Hendro. The success of an UKM is strongly influenced by the individual performance of its employees. The success of employee performance is the spearhead of the success of UKM itself. It also needs work motivation. Motivation will encourage employees to be more accomplished and productive. With the right motivation, employees will be encouraged to do their best in carrying out their duties. This study aims to determine the effect of motivation on the performance of employees of chips Cinta Mas Hendro. The sampling technique used purposive sampling technique. The number of samples as many as 100 employees of love chips. The research data were analyzed using PLS-SEM (Partial Least Square – Structural Equation Modeling) with SmartPLS 3 software. The results showed that indicators of work performance, fair wages, recognition of performance and challenging work have a positive influence on employee performance. Hendro while the responsibility indicator has a positive but not significant effect.